MICROCIRCULATORY AND TISSUE THEORY: INTEGRAL VISION OF CARCINOGENESIS - A. S. Dzasokhov (Креативная хирургия и онкология)
The brief  review  presents the  main  provisions  of  the  molecular-genetic theory  of carcinogenesis. The data  on the  presence of  overcelled  mechanisms regulating of  tissue homeostasis has done, which can be explained  by molecular  genetic  approach. The data of  the  interpretation of  the  theory  of  the  oncogene   based  on  different pathogenetic concepts is considered and  it allows you to continue the  development of tissue  theory  of carcinogenesis. The current understanding of the  structural and  functional characteristics of  the  microvasculature is described. Compelling   author’s  data  on the  effect of  oxygen therapy is provided  (normobaric and  hyperbaric  oxygen  therapy), and  the  modulation of antioxidant activity of plasma  by controlled differentiation of malignant cells with surgery (the change in the retrograde antegrade flow through the vascular reverse ).The significance of  microcirculation of  tissue  homeostasis has  determined. The updated position  of  the ground tissue microcirculatory theory  of carcinogenesis has formulated.